ANALISIS PENANDA GENDER BAHASA ARAB DALAM SIARAN AL-JAZEERA ARABIC “GENOSIDA DI JALUR GAZA” - Wulandari, Putri (Istiqra: jurnal hasil penelitian, 2025)
This study aims to analyze the use of Arabic gender markers in news broadcasts aired on one of the Al-Jazeera Arabic television stations, especially broadcasts related to the genocide that is currently happening in the Gaza Strip. The method in this study uses a qualitative-descriptive method. Data was carried out using the content analysis method. The findings in this study reveal that, first, news broadcasts on the Al-Jazeera Arabic station show Arabic gender markers in terms of syntax and morphology; second, Arabic gender markers in terms of syntax are the conformity of ism mudzakkar or ism muannast in the relationship between the subject and predicate to the sentence structure and the jama' mudzakkar sālim (ون) in the state of rafa' and the jama' mudzakkar sālim (ين) in the state of nasab and jar. Meanwhile, Arabic gender markers from a morphological perspective include the inflection process with ta’ ta’nist, the inclusion of the suffix (ات) in the jama’ muannast sālim and the suffixes (ون) and (ين) in the jama’ mudzakkar sālim. From this explanation, it is revealed that Al-Jazeera Arabic news broadcasts consistently apply gender markers in Arabic both syntactically and morphologically, especially in reporting the genocide in Gaza. This study shows how linguistic choices reflect social construction and gender representation in media narratives. So that in the future we can analyze the use of gender markers in the media and its impact on audience perceptions of gender representation in conflict news.